Social Media’s Impact on Indonesian Language Literacy Among SDN 1 Purbalingga Lor Students - Wuryanti, Siwi Tami; Suharto, Abdul Wachid Bambang (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
Literacy skills in the Indonesian language are defined as an individual's ability to understand, use, and analyse Indonesian in various contexts. With diverse features such as text, images, and videos, social media is considered capable of providing an interactive space for reading, writing, discussing, and enriching vocabulary and language comprehension. However, the use of social media by students is predominantly dominated by entertainment activities that offer minimal educational value. The content consumed often employs non-standard language, excessive abbreviations, or even disregards grammatical rules. This study employs descriptive qualitative research. The subjects of this research are 34 fifth-grade students from SDN 1 Purbalingga Lor, comprising 22 female and 12 male students. Data will be collected through three methods: observation, interviews, and literature review. The findings of this research indicate that social media has a complex influence on the Indonesian language literacy skills of students at SDN 1 Purbalingga Lor. The positive impacts of social media include the enhancement of language skills such as increased accessibility, language opportunities, and content creation. However, the challenges faced include the use of non-standard language, a decline in language skills, and difficulties in processing information, which can hinder formal learning.